Social Media Marketing and Bank Customers’ Behaviour: Conceptualizing a Relationship Model - et. al., C.D Mudondo, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
While research has underscored the benefits of social media marketing (SMM), organisations including commercial banks still fail to justify their continued investment in SMM, mainly because the full impact (of SMM) on customer behaviour remains unclear or largely researched. Thus, the aim of this paper was conduct an extensive literature review to develop a conceptual model to depict the proposed impact of social media marketing on commercial bank customers’ behaviour from a Social Exchange Theory (SET) perspective. Through an extensive review and synthesis of the literature on SMM, the researchers were able to theoretically postulate and propose the (possible) influence of the SET determinants inherent in SMM on commercial bank customers’ satisfaction, loyalty and their repurchase intentions. It is recommended that bank managers and marketers take cognizance of these (possible) proposed relationships, more specifically, the influence of the SET determinants inherent in SMM on bank customers’ behaviour. Furthermore, there is need to empirically evaluate the proposed conceptual model using data from a sample of bank customers and inferential statistics analytical techniques.